CONDITION OF ORAL CAVITY AND INDICATORS OF ENDOINTOXICATION IN SALIVA AMONG PATIENTS WITH CHRONIC RENAL FAILURE - Babayev, J.A. (World of Medicine and Biology, 2015)
Research of spectral substances in saliva of low and medium substances before and after hemodialysis was conducted among 20 patients with chronic renal failure. It was revealed, that among patients with chronic renal failure before hemodialysis the level of substances of low and medium molekular weight in saliva was increased on all researched wave length. After hemodialysis the reduction substances of low and medium molekular weight in range from 254 to 284 nm was noted, but in interval 294 and 304 an increase of substances of low and medium molekular weight was revealed, that is possible accociated with redistribution of low molecular subfraction in saliva.
Keywords: chronic renal failure; endointoxication; substances of low and medium molekular weight; saliva